2010
DOI: 10.1021/ja1097385
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Anti-Markovnikov Intermolecular Hydroalkoxylation of Terminal Acetylenes

Abstract: We report here the first transition-metal-catalyzed anti-Markovnikov intermolecular hydroalkoxylation of terminal acetylenes to give enol ethers in high yields without using bases. Arylacetylenes as well as alkenyl- and alkylacetylenes were coupled with aliphatic alcohols, and the products were obtained with high Z selectivity in most cases. Effective catalysts were 8-quinolinolato rhodium complexes, which are structurally simple but have been relatively unexplored as catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
46
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 40 publications
1
46
1
2
Order By: Relevance
“…The endo/exo-dig cyclic products are accessed throughi ntramolecular heteroannulations (Scheme 1). [10] In most cases, the products were obtained with high Z selectivity. [3] Enol ethers are important functionalities in organic synthesis and are used widely in cross-coupling,r ing-closing metathesis, and cycloaddition reactions and for the synthesis of pharmaceuticals.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…The endo/exo-dig cyclic products are accessed throughi ntramolecular heteroannulations (Scheme 1). [10] In most cases, the products were obtained with high Z selectivity. [3] Enol ethers are important functionalities in organic synthesis and are used widely in cross-coupling,r ing-closing metathesis, and cycloaddition reactions and for the synthesis of pharmaceuticals.…”
mentioning
confidence: 98%
“…[1] Significant advancements have been made toward selective formation of the Markovnikov/anti-Markovnikov products for the direct intermolecular addition of amines,a cids, thiols, and various other nucleophilic substrates to alkynes. [10] In most cases, the products were obtained with high Z selectivity. [2] However,addition reactions of weak nucleophiles such as water and alcohol remain achallenging task.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has recently reported anti-Markovnikov addition of alcohols, 11 secondary amines 12 as well as the [2+2] cycloaddition of electron-deficient alkenes 13 to terminal alkynes catalyzed by 8-quinolinolato rhodium complex systems. During the course of these studies, the formation of alkyne oligomers as by-products was observed.…”
mentioning
confidence: 99%